Is the polarity of the Co3O4(111) surface compensated by electron transfer from bulk donor defects? - Gurrath, Martin; Schlott, Hannah; Meyer, Bernd (Surface Science, 2023)
Experimental studies have shown that the Co3O4(111) surface exists as an unreconstructed (1 × 1) truncated bulk termination. Polarity compensation of this polar surface thus has to occur by a transfer of electrons, which creates partially occupied valence states and makes the surface metallic. Here we show by Hubbard-U corrected density-functional theory calculations that such a polarity compensation mechanism would make the surface highly reactive, which is not in agreement with experimental observations. An additional compensation mechanism has to be at work, by which the partially occupied valence band states are filled by electrons without requiring a reconstruction of the surface. As such an mechanism we propose the transfer of electrons from bulk donor defects to the surface. By employing this mechanism in our calculations we recover the experimentally observed reactivity. This demonstrates that for all polar surfaces, which are fully or partially polarity compensated by the transfer of electrons, additional electronic effects have to be considered in any electronic structure calculation in order to capture the correct surface chemistry.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Charge neutralization; Cobalt oxide; Density-functional theory; Polar surfaces